Childhood simple obesity and erythrocyte sedimentation rate - Onur Kutlu, Nurettin; Gulcan, Hande; Yakinci, Cengiz; Yologlu, Saim (Annals of Medical Research, 2021)
None
Keywords: s : Erythrocyte sedimentation rate, child, obesity